2014
DOI: 10.1016/j.ijrobp.2013.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Standing on the Shoulders of Giants: Results From the Radiation Oncology Academic Development and Mentorship Assessment Project (ROADMAP)

Abstract: Purpose To analyze survey information regarding mentorship practices and cross-correlate the results with objective metrics of academic productivity among academic radiation oncologists at U.S. ACGME-accredited residency training programs. Methods and Materials An IRB-approved survey for the Radiation Oncology Academic Development and Mentorship Assessment Project (ROADMAP) was sent to 1031 radiation oncologists employed at an ACGME-accredited residency training program and administered using Research Electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 20 publications
1
16
0
2
Order By: Relevance
“…33 Other studies have pointed out that although these measures might improve life satisfaction, they might not necessarily prevent burnout. 34 The prevalence of stress and burnout among radiation oncologists poses the question whether they should undergo regular screening, especially because medical practitioners, in general, often do not seek help for themselves.…”
Section: Discussionmentioning
confidence: 99%
“…33 Other studies have pointed out that although these measures might improve life satisfaction, they might not necessarily prevent burnout. 34 The prevalence of stress and burnout among radiation oncologists poses the question whether they should undergo regular screening, especially because medical practitioners, in general, often do not seek help for themselves.…”
Section: Discussionmentioning
confidence: 99%
“…surveyed female surgeon academics and found positive relationships between having an informal mentor and various indicators of objective career success, such as number of publications and research awards obtained. Similarly,Holliday, Jagsi, Thomas, Wilson, and Fuller (2014) reported positive associations between mentoring received and various productivity metrics (e.g., number of publications and citations, h-index) in a sample of academic radiation oncologists. Similarly, a mixed-methods study found that mentoring contributed to the professional advancement of academic protégés through opportunities for career and leadership development, learning from a role model, building professional relationships, and increased job satisfaction(Ambler, Harvey, & Cahir, 2016).…”
mentioning
confidence: 84%
“…Durch Mentoren-Programme können die ÄiW sowohl auf akademischer als auch psychosozialer Ebene unterstützt und interpersonelle und kommunikative Fähigkeiten verbessert werden [21]. Gutes Mentoring in Kombination mit einer gut organisierten Weiterbildung durch das Kompetenzzentrum kann zur Verkürzung der Weiterbildungsdauer führen [13] und entscheidenden Einfluss auf Karriereentwicklung und akademische Leistungen nehmen [22]. Nach Hoffmann et al [23] beziehen sich die häufigsten an einen Mentor gestellten Fragen auf die Themen Stellengesuche, Bewerbung, Arbeitsverträge, Weiterbildungsrichtlinien, aber auch zu 10 % auf individuelle Schwierigkeiten und Probleme.…”
Section: Diskussionunclassified